Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Dumping Limbah (B3) Tanpa Izin - Medd, Laura; Harriestha, Putu Ade (Kertha Wicara : Journal Ilmu Hukum, 2020)
Kata Kunci : Dumping Limbah B3 ,Lingkungan Hidup, Pertanggungjawaban Pidana.   ABSTRACT The intent of this article aims arrangement of disposal cases of waste dumping hazardous and toxic substances (B3) without permission can pollution in environmental media. Unlicensed waste disposal often occurs due to one of them due to increasing industrial activity, giving the intention of the perpetrator to deliberately dispose of waste to the environmental media due to the amount of waste that a lot so it requires cost for processing. This is contrary to the provisions of Article 59 Act No. 32 year 2009 on protection and environmental management with the regulation of the implementation of government regulation number 101 of 2014 about waste management of hazardous and toxic materials and will be subject to criminal sanctions against the perpetrators to provide a deterrent effect. This research uses normative legal research ordinances with an invitation approach as well as research into related documents. The study showed that criminal liability of the perpetrators of dumping waste (B3) without permission is closely related to the element of error because a person cannot be sentenced when there is no fault factor whether it is intentional or misshapness.   Keywords : Toxic and Hazardous Waste , Environment, criminal liability.